SURGICAL CORRECTION OF ATRESIA ANI WITH RECTOVAGINAL FISTULA IN LAMBS - A REVIEW OF FIVE CASES - P. Tamilmahan; B. Bharathidasan; M. Ranjithkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A total of five lambs, 6-8 months old were presented with the history of faeces voiding through vulva and absence of anal opening since birth. Clinical examination revealed a fistulous tract connecting dorsal vaginal wall and rectum. Animal passing small quantity of dung with straining frequently due to small opening. Cases were tentatively diagnosed as congenital rectovaginal fistula with atresia ani. Surgical correction was attempted. All the animals recovered without any complications.